2017
DOI: 10.3390/ph10030068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Metastases in Patients with Prostate Cancer—A Comparison between 99mTc-Bone-Scintigraphy and [68Ga]Ga-PSMA PET/CT

Abstract: Purpose: Bone scintigraphy is the standard of reference in bone metastases in prostate cancer patients. However, new radiotracers employed in prostate-specific membrane antigen (PSMA)-ligands has led to the growing importance of PET/CT as diagnostic tool. The aim of our study was to investigate the difference between bone scan and PSMA-PET/CT for the detection of bone metastases in prostate cancer. Methods: Thirty patients with bone metastases originating from prostate cancer were examined by 99mTc-MDP bone sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…PSMA PET/CT may represent a more promising imaging biomarker for this purpose because of its high sensitivity and specificity in detecting metastases after biochemical relapse of prostate cancer (12,13) and the increasing availability of the method. Consistently, a recent study indicated the superiority of PSMA PET/CT over conventional bone scintigraphy in the detection of bone metastases (14).…”
supporting
confidence: 52%
“…PSMA PET/CT may represent a more promising imaging biomarker for this purpose because of its high sensitivity and specificity in detecting metastases after biochemical relapse of prostate cancer (12,13) and the increasing availability of the method. Consistently, a recent study indicated the superiority of PSMA PET/CT over conventional bone scintigraphy in the detection of bone metastases (14).…”
supporting
confidence: 52%
“…This could be explained due to the small number of patients in the single groups. Therapy assessment with PSMA 11‐PET has been investigated before in patients undergoing radium‐223 therapy . Here, the PSMA 11‐PET seemed to overcome the known limitations of BS and other established PET tracers.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have already reported comparisons between 68 Ga-PSMA PET/ CT and planar BS with (24) or without (25,26) routinely performed SPECT. These reports had some remarkable limitations; for example, the mean intervals between the imaging modalities were 21 d (range not reported) (25), up to 80 d (24), or up to 100 d (26).…”
Section: Discussionmentioning
confidence: 99%